2019
DOI: 10.1039/c8cp06354k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of benzene excimer formation from the parallel-displaced dimer

Abstract: Charge transfer, exciton localization and time scales in benzene excimer formation after a S0–S1 transition from the parallel-displaced structure were characterized by surface-hopping dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…However, these results for the Rot1-S0 are not in agreement with the ones presented in this study or those reported by Schouder et al 26 The DS1-S1 geometry should be sufficiently close to an eclipsed geometry to allow the latter to be reached, should it be more stable. However, given the relevance of eclipsed D2h structure for aromatic excimers, 38,42 besides parallel displaced ones, 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results for the Rot1-S0 are not in agreement with the ones presented in this study or those reported by Schouder et al 26 The DS1-S1 geometry should be sufficiently close to an eclipsed geometry to allow the latter to be reached, should it be more stable. However, given the relevance of eclipsed D2h structure for aromatic excimers, 38,42 besides parallel displaced ones, 21…”
Section: Resultsmentioning
confidence: 99%
“…31 In addition to the doubly excited state, other types of states have also been proposed as relevant for the singlet fission process, and a recent study by Suarez et al 9 used descriptors [32][33][34] based on the firstorder transition density matrix (1TDM) to study the importance of charge-transfer and charge-resonance states in this process for dimer conformations relevant for solid-state tetracene. This same technique can be applied to analyze the relevant interactions in the excimer survival process, [35][36][37] and, recently, Cardozo et al 38 demonstrated through nonadiabatic excited-state dynamics the prominent role of intermolecular charge transfer in the excimer formation process for a benzene dimer.…”
Section: Introductionmentioning
confidence: 99%
“…As an additional challenge, the required theory has to simultaneously describe with high accuracy the weak dispersion forces between the subunits, during non-equilibrium processes, and the relaxation dynamics involving multiple and sometimes coupled electronic states. [60][61][62][63][64][65][66] From the modeling perspective, p-stacked CT systems also require a very good description of both non-covalent interactions and spatially delocalized excitations (i.e., valence-Rydberg, doubly excited, pp*). In this context, we propose to study the model system via ab initio molecular dynamics simulations (AIMD) [67][68][69][70][71] for the ground and the excited state in which energies and forces are computed within methods rooted in Density Functional Theory (DFT) and its time-dependent extension (TD-DFT) for the excited state properties.…”
Section: Introductionmentioning
confidence: 99%
“…23 A thorough investigation of excimer formation in tetracene thus seems to be mandated. Recently, the excimer formation of benzene was studied in detail experimentally by Fuji et al 24 and by simulation by the groups of Krylov 25 and Cardozo 26 . The excimer formation dynamics was also studied in larger systems like bay-tethered perylene bisimides by Würthner et al, where a single relaxation pathway to the excimer state was found.…”
Section: Introductionmentioning
confidence: 99%